Lupeol protect against LPS-induced neuroinflammation and amyloid beta in adult mouse hippocampus - Choe, Kyonghwan; Park, Jun Sung; Park, Hyun Young; Tahir, Muhammad; Park, Tae Ju; Kim, Myeong Ok (Frontiers in Nutrition, 2024)
Neuroinflammation includes the activation of immune glial cells in the central nervous system, release pro-inflammatory cytokines, which disrupt normal neural function and contribute to various neurological disorders, including Alzheimer's disease (AD), Parkinson's disease, multiple sclerosis, and stroke. AD is characterized by various factors including amyloidogenesis, synaptic dysfunction, memory impairment and neuroinflammation. Lipopolysaccharide (LPS) constitutes a vital element of membrane of the gram-negative bacterial cell, triggering vigorous neuroinflammation and facilitating neurodegeneration. Lupeol, a naturally occurring pentacyclic triterpene, has demonstrated several pharmacological properties, notably its anti-inflammatory activity. In this study, we evaluated the antiinflammatory and anti-Alzheimer activity of lupeol in lipopolysaccharide (LPS)-injected mice model. LPS (250ug/kg) was administered intraperitoneally to C57BL/6N male mice for 1 week to induce neuroinflammation and cognitive impairment. For biochemical analysis, acetylcholinesterase (AChE) assay, western blotting and confocal microscopy were performed. AChE, western blot and immunofluorescence results showed that lupeol treatment (50mg/kg) along with LPS administration significantly inhibited the LPS-induced activation of neuroinflammatory mediators and cytokines like nuclear factor (NF-κB), tumor necrosis factor (TNF-α), cyclooxygenase (COX-2) and interleukin (IL-1β). Furthermore, we found that LPS-induced systemic inflammation lead to Alzheimer's symptoms as LPS treatment enhances level of amyloid beta (Aβ), amyloid precursor protein (APP), Beta-site APP cleaving enzyme (BACE-1) and hyperphosphorylated Tau (p-Tau). Lupeol treatment reversed the LPS-induced elevated level of Aβ, APP, BACE-1 and p-Tau in the hippocampus, showing anti-Alzheimer's properties. It is also determined that lupeol prevented LPS-induced synaptic dysfunction via enhanced expression of pre-and post-synaptic markers like SNAP-23, synaptophysin and PSD-95. Overall, our study shows that lupeol prevents memory impairment and synaptic dysfunction via inhibition of neuroinflammatory processes. Hence, we suggest that lupeol might be a useful therapeutic agent in prevention of neuroinflammation-induced neurological disorders like AD.